Pengaruh Fraksi Volume Serat Terhadap Peningkatan Kekuatan Impak dan Kekuatan Tarik Komposit Berpenguat Serat Daun Nanas (Ananas Cosmosus) - Zahrani, Amilia; Sayuti, Muhammad; Zulnazri, Zulnazri; Putra, Reza; Islami, Nurul (Malikussaleh Journal of Mechanical Science and Technology, 2024)
A composite is a technical material that is made by combining two or more materials that have different properties to become a new material with different properties. Natural fibers used as composite reinforcement are more environmentally friendly and biodegradable. The use of natural fibers as composite reinforcement in recent years has experienced very rapid development. One of them is pineapple leaf fiber. The aim of this research is to determine the effect of fiber volume fraction and NaOH immersion on the mechanical properties (Tensile Strength and Impact Strength) of composites reinforced with pineapple leaf fibers with an epoxy matrix. In this research, woven composites were made with variations in volume fraction and NaOH immersion time for the fibers, then tensile tests according to ASTM D-3039 standards and impact tests according to ASTM D256 standards. Based on test results with varying fiber volume fractions of 15%, 20%, and 25%, the strength results increase and decrease. The tensile strength of the composite tends to increase with increasing fiber volume fraction and NaOH immersion. However, the longer the soaking time, namely 4 hours, the tensile strength of the composite tends to decrease. The most optimal average value of tensile strength is at a fiber volume fraction of 25% with fiber soaking for 2 hours with a value of 23.07 MPa and the lowest average value of tensile strength is at a fiber volume fraction of 15% with fiber soaking for 4 hours with value 11.31 MPa. Meanwhile, the highest average impact value was owned by a composite with a fiber volume fraction of 20% without soaking, namely 0.0589 j/mm2 and the lowest impact value was with a fiber volume fraction of 20% with fiber soaking for 4 hours, namely 0.0124 j/mm2.